Spectrophotometric, voltammetric and cytotoxicity studies of 2-hydroxy-5-methoxyacetophenone thiosemicarbazone and its N(4)-substituted derivatives: A combined experimental-computational study - AKKİPRİK, MUSTAFA; ÖZBAŞ, SUNA (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In this study, 2-hydroxy-5-methoxyacetophenone thiosemicarbazone (HMAT) and its novel N(4) substituted derivatives were synthesized and characterized by different techniques. The optical band gap of the compounds and the energy of HOMO were experimentally examined by UV-vis spectra and cyclic voltammetry measurements, respectively. Furthermore, the conformational spaces of the compounds were scanned with molecular mechanics method. The geometry optimization, HOMO and LUMO energies, the energy gap of the HOMO LUMO, dipole moment of the compounds were theoretically calculated by the density functional theory B3LY10/6-3114-+G(d,p) level. The minimal electronic excitation energy and maximum wavelength calculations of the compounds were also performed by TD-DFT//B3LYP/6-311++G(d,p) level of theory. Theoretically calculated values were compared with the related experimental values. The combined results exhibit that all compounds have good electron-donor properties which affect anti-proliferative activity. The cytotoxic effects of the compounds were also evaluated against HeLa (cervical carcinoma), MCF-7 (breast carcinoma) and PC-3 (prostatic carcinoma) cell lines using the standard MIT assay. All tested compounds showed antiproliferative effect having IC50 values in different range. In comparison with that of HMAT, it was obtained that while ethyl group on 4(N)-substituted position decreased in potent anti-proliferative effect, the phenyl group on the position increased in anti-proliferative effect for the tested cancer cell line. Considering the molecular energy parameters, the cytotoxicity activities of the compounds were discussed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Thiosemicarbazone; UV-vis spectroscopy; Cyclic voltammetry; DFT calculations; Cytotoxicity; ANTICANCER DRUG; SEMICARBAZONES; COMPLEXES; ANTIFUNGAL; AGENTS; DNA